The association between stress hyperglycemia ratio and 1-year outcomes in patients with acute myocardial infarction: a retrospective large sample cohort study - Yan, Ning; Wu, Peng; Zhang, Zhengjun; Wang, Mohan; Ma, Juan; Ma, Ali; Chen, Dapeng; Ma, Xueping; Li, Xiaocheng (Frontiers in Endocrinology, 2025)
BackgroundThe Stress Hyperglycemia Ratio (SHR) is associated with poor outcomes in coronary artery disease patients, but its link to Acute Myocardial Infarction (AMI) prognosis is unclear. This study explores the relationship between SHR and 1-year outcomes after AMI using a large cohort analysis.MethodsThis retrospective study enrolled 4012 AMI patients from General Hospital of Ningxia Medical University(2016-2019). These patients were stratified into three distinct groups according to the tertiles of the SHR: Group T1 (SHR < 0.90, n=1337), Group T2 (0.90 ≤ SHR < 1.11, n=1337), and Group T3 (SHR ≥ 1.11, n=1338). All patients were clinically followed for 1-years to collect major adverse cardiovascular and cerebrovascular events (MACCE). After controlling for different confounding factors, cox regression models and restricted quadratic splines were used to investigate the relationship between SHR and 1-years clinical outcomes.ResultsDuring the 1-year follow-up, 229 all-cause deaths were recorded, yielding a mortality rate of 5.71% (n=229). Additionally, 861 MACCE were recorded, yielding a MACCE rate of 21.46%. After adjusting for covariates, SHR was found to be significantly associated with 1-year MACCE [hazard ratio (HR) = 2.18; 95% confidence interval (CI) = 1.64-2.89; P < 0.001] and all-cause mortality (HR = 3.11; 95% CI = 1.77-5.46; P < 0.001) in patients with AMI, and the T3 group exhibited a higher risk of 1-year MACCE (HR = 1.67; 95% CI = 1.34-2.09; P < 0.001) and all-cause mortality (HR = 1.67; 95% CI = 1.02-2.73; P =0.042) compared with T1 group. A J-shaped relationship was observed between SHR and 1-year MACCE as well as all-cause mortality, showing a turning point at 0.87. Beyond this threshold, the hazard ratio for 1-year MACCE was 2.64 (95% CI: 1.91-3.65), and for all-cause mortality was 4.26 (95%: CI 2.30-7.86). The results remained consistent across subgroup.ConclusionSHR is significantly and positively associated with one-year clinical outcomes in patients with AMI. Furthermore, there is a specific non-linear association between SHR and MACCE and all-cause mortality (both inflection point 0.87). Interventions aimed at reducing SHR levels below 0.87 through medication management have the potential to significantly improve outcomes.